Epigenome-wide association study of lung function level and its change. Issue 1 (4th July 2019) - Imboden, Medea; Wielscher, Matthias; Rezwan, Faisal I.; Amaral, André F.S.; Schaffner, Emmanuel; Jeong, Ayoung; Beckmeyer-Borowko, Anna; Harris, Sarah E.; Starr, John M.; Deary, Ian J.; Flexeder, Claudia; Waldenberger, Melanie; et al.
Previous reports link differential DNA methylation (DNAme) to environmental exposures that are associated with lung function. Direct evidence on lung function DNAme is, however, limited. We undertook an agnostic epigenome-wide association study (EWAS) on pre-bronchodilation lung function and its change in adults. In a discovery–replication EWAS design, DNAme in blood and spirometry were measured twice, 6–15 years apart, in the same participants of three adult population-based discovery cohorts (n=2043). Associated DNAme markers (p<5×10 −7 ) were tested in seven replication cohorts (adult: n=3327; childhood: n=420). Technical bias-adjusted residuals of a regression of the normalised absolute β-values on control probe-derived principle components were regressed on level and change of forced expiratory volume in 1 s (FEV1 ), forced vital capacity (FVC) and their ratio (FEV1 /FVC) in the covariate-adjusted discovery EWAS. Inverse-variance-weighted meta-analyses were performed on results from discovery and replication samples in all participants and never-smokers. EWAS signals were enriched for smoking-related DNAme. We replicated 57 lung function DNAme markers in adult, but not childhood samples, all previously associated with smoking. Markers not previously associated with smoking failed replication. cg05575921 ( AHRR (aryl hydrocarbon receptor repressor)) showed the statistically most significant association with cross-sectional lung function (FEV1 /FVC: pdiscovery =3.96×10 −21 and pcombined =7.22×10 −50 ). A score combining 10 DNAme markers previously reported to mediate the effect of smoking on lung function was associated with lung function (FEV1 /FVC: p=2.65×10 −20 ). Our results reveal that lung function-associated methylation signals in adults are predominantly smoking related, and possibly of clinical utility in identifying poor lung function and accelerated decline. Larger studies with more repeat time-points are needed to identify lung function DNAme in never-smokers and in children. An agnostic association study on lung function using longitudinal population-based cohort data shows that differentially methylated genomic sites related to smoking are strongly associated with lung function in adults http://ow.ly/wYID30onUB4